Fuel cell technology handbook - Hoogers, Gregor (CRC Press, 2003)
Annotation The principle behind fuel cells remains unchanged since 1839. It is "an electrochemical 'device' that continously converts chemical energy into electric energy" and when hydrogen is used as fuel it emits only power and water. Hoogers (Trier U. of Applied Sciences, Germany) presents a handbook introducing fuel cell technology and its applications. After giving an outline of the history of fuel cell technology, he reviews the main concepts, development strands, and remaining technical problems with respect to the overall fuel cell system. The applications of fuel cell technology in automotive, stationary, and portable power generation is then reviewed. Finally, competing technologies are assessed. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Fuel cells.; elektronické knihy; electronic books